Public-private partnership in education: Features and prospects - V. Varkulevich, Tat'jana (2019)
Effective and constructive interaction of the state and business is an essential condition for the country's socio-economic development. One of the tools to ensure the growth of the financial, innovation, technological potential of the territories is the implementation of public-private partnership projects (hereinafter - PPP). The modern market system creates the conditions for the organization of cooperation of market entities in all sectors and areas, including in the field of education. Within this article, a comprehensive review of the PPP typology, structured on the basis of the multidimensionality of the classifications proposed by the authors, was conducted. Special attention is paid to the typology of partnership in the field of education, which has become widespread and has been actively implemented in Russia for the last five years. Based on the review of typologies of public-private partnerships in education, the main criteria were identified, by which the types of partnerships were classified, the main distinguishing features of PPP in education were formulated, the basic principles characteristic of PPP projects were identified, and the prospects and benefits that the sphere education from participation in public-private partnership.